ARSITEKTUR VERNAKULAR INDONESIA Perannya Dalam Pengembangan Jati Diri - Wiranto Wiranto (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 1999)
Vernacular architecture is derived from The Folk Architecture.The Folk Architecture is born by the ethnical community ,anchored by tradition. Vernacular architecture usually concerned with the cosmology,way of life and life style of the ethnical community, it would be an alternative answer of modernization. Modernization,the development of Technology and the social-economical interaction would like to get some modern needs .Vernacular Architecture is a translation of tradition and also it haves identities which can be increased by inovation and creativity in syncretism or eclectism.The syncretism or eclectism of Indonesian vernacular architecture would be a strand of post modernism in the form of Neo-Vernacular architecture. Vernacular architecture have been proposed as one of the vehicles toward the evolution of Indonesian architecture with National identity. Abstract in Bahasa Indonesia : Arsitektur Vernakular tumbuh dari arsitektur rakyat,yang lahir dari masyarakat etnik dan berjangkar pada Tradisi etnik.Dengan demikian Arsitektur tersebut sejalan dengan paham kosmologi,pandangan hidup, gaya hidup dan memiliki tampilan khas sebagai cerminan jati diri yang dapat dikembangkan secara inovatif kreatif dalam pendekatan sinkretis ataupun eklektis. Modernisasi dan kemajuan teknologi serta interaksi sosial ekonomi menuntut kehadiran Arsitektur yang mampu berdialog dengan tuntutan baru.Sinkretisme .arsitektur vernakular Indonesia merupakan potensi yang memberi sumbangan pada